Answer:
(-5,-7); m=-2 : y = -2x - 17
(-4,2); m=2 : y = 2x + 10
Explanation:
Since we only have a point and the slope. Then we can write the equations in point-slope form [(y - y₁) = m(x - x₁)], the convert to slope-intercept form ( y = mx + c ).
For (-5,-7); m = -2:
Write the equation in point-slope form
y - (-7) = - 2 (x - (-5))
y + 7 = -2 ( x + 5 )
Transpose to determine slope-intercept form
since y + 7 = -2 ( x + 5 )
y = -2 x - 10 - 7
y = -2x - 17
For (-4,2); m=2 :
Write the equation in point-slope form
(y - 2) = 2 (x - (-4))
y - 2 = 2 ( x + 4 )
Transpose to determine slope-intercept form
since y - 2 = 2 ( x + 4 )
y = 2 x + 8 + 2
y = 2x + 10